Determination of the Dosimetric Characteristics of BATAN’s 125I Source for Brachytherapy: An Experimental Study - K.Y.P. Sandy; S.A. Pawiro; D.S. Soejoko (Atom Indonesia, 2018)
125I brachytherapysources withlowphotonenergies have beenwidelyusedin treatingtumors.Accordingto American Association of Physicists in Medicine Task Group No. 43 (AAPMTG-43)recommendations,dosimetric characteristic ofthe newbrachytherapysources shouldbe determined before clinical use.Inthis study, dosimetric characteristic of 125Imanufacturedby BATAN have been determined through measurement by using Thermoluminescent Dosemeter (TLD) andgafchromic XR- QA2film.The radial dosefunctionmeasurements were performedat distances rangingfrom0.5to10cmfromthe source center.The anisotropyfunctions were measuredat distances of2,3,and5cmfromthe source center forangles ranging from0to 90degree inallquadrants.The results indicated that a doserate constants measured with TLD and film are 1.05± 8 % cGy.h-1.U-1and1.01±8 % cGy.h-1.U-1, respectively.The radial dosefunctiondecreasesalongwith the increasingdistance from source andmeetsthe 5thorderpolynomial equation. The anisotropyfunction resultshows thattheanisotropyindosedistributionincreasesalongthe source axis.Thismeasurement data areinagreementwith the previousstudy on EGSnrc Monte Carloresult andhave a similar patternwithIsoAidandGMS BT-125 commercial125Isource.